Metal–Organic‐Framework‐Templated Polyelectrolyte Nanocapsules for the Encapsulation and Delivery of Small‐Molecule–Polymer Conjugates. Issue 12 (1st June 2016) - Liu, Shuo; Chen, Jianbin; Bao, Xiaojia; Li, Tao; Ling, Yunyang; Li, Chunxiang; Wu, Chuanliu; Zhao, Yibing
Abstract: Herein, we report a strategy for exploiting nanoscale metal–organic frameworks (nano‐MOFs) as templates for the layer‐by‐layer (LbL) assembly of polyelectrolytes. Because small‐molecule drugs or imaging agents cannot be efficiently encapsulated by polyelectrolyte nanocapsules, we investigated two promising and biocompatible polymers (comb‐shaped polyethylene glycol (PEG) and hyperbranched polyglycerol‐based PEG) for the conjugation of model drugs and imaging agents, which were then encapsulated inside the nano‐MOF‐templated nanocapsules. Furthermore, we also systemically explored the release kinetics of the encapsulated conjugates, and examined how the encapsulation and/or release processes could be controlled by varying the composition and architecture of the polymers. We envision that our nano‐MOFs‐templated nanocapsules, through combining with small‐molecule–polymer conjugates, will represent a new type of delivery system that could open up new opportunities for biomedical applications. Abstract : Honey comb : A new nano‐metal–organic framework (MOF)‐templated polyelectrolyte nanocapsule can be exploited for the encapsulation of comb‐shaped small‐molecule–PEG‐copolymer conjugates. The combination of nano‐MOF‐templated nanocapsules and small‐molecule–polymer conjugates represents a new type of multi‐stage delivery system.